Professional React Native Expert Techniques and Solutions for Building High-Quality, Cross-platform, Production-ready Apps - Kuttig, Alexander Benedikt (Packt Publishing, Limited, 2022)
Learn how React Native works under the hood and what this means for building large-scale, cross-platform, production-ready applications without compromising on the quality and performance Key Features Explore a modern approach to React Native, covering state management, animations, gestures, and more Implement best practices and practical techniques for creating large-scale, production-ready apps Create a development process including workflow automation with GitHub Actions, Fastlane, and Bitrise Book Description The React Native framework offers a range of powerful features that make it possible to efficiently build high-quality, easy-to-maintain frontend applications across multiple platforms such as iOS, Android, Linux, Mac OS X, Windows, and the web, helping you save both time and money. And this book is your key to unlocking its capabilities. Professional React Native provides the ultimate coverage of essential concepts, best practices, advanced processes, and tips for everyday developer problems. The book makes it easy to understand how React Native works under the hood using step-by-step explanations and practical examples so you can use this knowledge to develop highly performant apps. As you follow along, you'll learn the difference between React and React Native, navigate the React Native ecosystem, and revisit the basics of JavaScript and TypeScript needed to create a React Native application. What's more, you'll work with animations and even control your app with gestures. Finally, you'll be able to structure larger apps and improve developer efficiency through automated processes, testing, and continuous integration. By the end of this React native app development book, you'll have gained the confidence to build high-performance apps for multiple platforms, even on a bigger scale. What you will learn Become familiar with how React Native works under the hood Understand how to make the most of React Native for app development Explore different approaches to building apps across various platforms Become familiar with process automation and automated testing Contribute to open source code and structure your own code library Understand how to set up the architecture for bigger React Native projects Who this book is for This book is for developers who want to get started with React Native as well as experienced React Native developers interested in building professional cross-platform applications. Familiarity with the basics of JavaScript (including its syntax) and general software engineering concepts, such as data types, control flows, and server/client structures, is required. Although useful, experience with React Native is not necessary.